Мотиваційний тренінг у процесі професійної підготовки фахівців - Нікітіна, Ірина Всеволодівна (My University, 2015)
У статті проаналізовано динаміку професійної мотивації, психологічні умови її формування у процесі професійної підготовки майбутніх фахівців, визначено ключові механізми розвитку особистісної причинності. Встановлено взаємозв’язок процесів мотивації та розвитку суб’єктності особистості студента. Представлено тренінгові програму для студентів «Мотиваційний тренінг». This article analyzes the development dynamic of the professional motivation, psychological factors of its formation in the process of professional training of the future specialist . The main mechanisms of the individual causality determined in the personality oriented education. A leading role in the process of the professional becoming and personality growth is played a subjects activity of the students .The professional self-realization of the future specialist is predefined his readiness to the professional motivation on the base of subjects activity growth. Connection between the professional motivation of student and his activity as the subject of self- perfections in our research. Today’s reforms of the Ukrainian higher education need for radical change of traditional system of young people’s training for the optimum self- development and self-realization of their individual potential on the base of personality motivational growth. The result of this investigation is training program “Skills of the formation of the professional motivation“.
Keywords: кафедра гуманітарних дисциплін; розвиток; професійна мотивація; суб’єктна активність; особистісна причинність; тренінг формування мотивації; development; professional motivation; subjects activity; individual causality; training of the professional motivation